Cord blood processing by a novel filtration system. (12th October 2015) - Sato, N.; Fricke, C.; McGuckin, C.; Forraz, N.; Degoul, O.; Atzeni, G.; Sakurai, H.
Abstract: Objectives: Availability of cord blood (CB) processing has been limited by the need for electrically aided centrifugal techniques, which often produce only low final cell product yield. Here, we describe development and characterization of a novel filter device aimed at allowing CB processing, using gentle gravity‐led flow. Materials and methods: CB was processed with a novel filter device (CellEffic CB, consisting of non‐woven fabric), without any centrifugation. Cells were harvested by flushing the filter with either HES or physiological saline solution (SALINE). Differential cell counts and viability analysis, combined with Fluorescence‐Activated Cell Sorting (FACS) (total nucleated cells [TNC], mononuclear cells [MNC], CD45+ CD34+ cells, hematopoietic precursor cells [HPCs]) and clonogenic assay, were employed for analysis of CB pre‐ and post‐processing, and after freeze/thawing. Results: Processing using the novel filter yielded high quality RBC depletion while maintaining good recovery of TNC, MNC, CD34+, HPCs and colony forming unit (CFU) output. The filter performed equally well using HES or SALINE. Gravity‐led flow provided gentle cell movement and protection of the stem cell compartment. Post‐thaw CFU output was maintained particularly, an important indicator for CB banking. Conclusions: Geographical limitations of CB transplantation and banking have required a non‐electrical, non‐centrifugal solution. This novel filter CellEffic CB device revealed rapid yet gentle cell processing while maintaining the stem/progenitor cell compartment required for both haematological and regenerative medicine therapies.